Laser-induced modulation of Magnon and Phonon excitations: Size and defect dependency in antiferromagnetic NiO nanoparticles with rhombohedral distortion - Adiba Adiba; Ph Nonglen Meitei; Tufail Ahmad (Next Nanotechnology)
NiO nanoparticles were synthesized using jasmine flower and orange peel. The transition from cubic to rhombohedral phase was observed with peak splitting in the XRD patterns as the annealing temperature increased. Differences in the annealing environment resulted in particles with different crystallite sizes and amounts of nickel vacancy, directly impacting their magnetic properties. Notably, particles below 30 nm exhibited weak ferromagnetism, while those above 30 nm showed antiferromagnetic properties. Moreover, the power of the laser was tuned to 5 mW to achieve the disappearance of the 2 M peak. A key highlight of this work is the identification of the transverse acoustic phonon mode and the splitting of the transverse optical (TO) mode in NiO.